The Philippines life, death and revolution [videorecording]. ([New York] Downtown Community TV Center)
A documentation of the urban poor's fight for survival. It also shows how the insurgents manage to live.
VHS
Keywords: Urban poor -- Philippines; Insurgency -- Philippines; Sociology